Sport Tourism: The Urgency of Maybank Marathon as an International Event to Promote Balinese Tourism and Culture - Murtono, Putu Agus; Sagita Jaya Utama, I Putu Sagita Jaya Utama; Ardana, I Komang (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2024)
The purpose of this study is to determine the urgency of the Maybank Marathon as an international event in advancing Balinese tourism and culture. The method used to analyze the problems in this study is descriptive qualitative where researchers conducted various interviews with marathon participants and the community in Bali. The results of this study indicate that the urgency of sport tourism can be seen from the economic impact that arises where the resources involved will affect the economic movement in an area. This will also have an impact on the various investments that are present so that sport tourism is able to create maximum economic movement for an area. The existence of the Maybank Marathon as an international event will certainly affect the image and identity of Bali where this mechanism will emphasize that there is an introduction from outside nations to get to know Bali better so that they attract attention and interest to always visit Bali. In other words, it can be concluded that sports tourism is able to create benefits where areas can be promoted according to the potential of the area so that good marketing will certainly attract foreign tourists to visit the city of Bali.